From 1D microbiological assays to 3D advanced skin models: enhancing preclinical strategies to unravel the impact of bioactive textiles on the human skin microbiome - Negut, Irina; Mazzanti, Camilla; Laurano, Rossella; Ciardelli, Gianluca; Bronco, Simona; Oliveira, Cláudia S. (Frontiers in Cellular and Infection Microbiology, 2025)
Bioactive textiles have emerged as multifunctional materials to actively interact with the human skin and its microbiome. By embedding natural or synthetic bioactive compounds, such as chitosan, essential oils, plant extracts, and metallic nanoparticles, these materials aim to prevent and target infections, modulate inflammation, and promote skin homeostasis. Given the critical role of the skin microbiome in maintaining barrier integrity and immune balance, strategies that selectively inhibit pathogenic microorganisms (e.g., Staphylococcus aureus, Cutibacterium acnes) while preserving beneficial commensals like Staphylococcus epidermidis are essential to avoid dysbiosis and associated dermatological disorders. This review highlights current trends in the design and functionalization of bioactive textiles, emphasizing sustainable and biocompatible approaches that leverage natural antimicrobial compounds and green synthesis techniques. It also examines conventional evaluation pipelines primarily based on 1D microbiological assays and 2D skin models, highlighting their limitations in predicting real-world performance. Advanced in vitro models, particularly 3D reconstructed human skin platforms incorporating both pathogenic and commensal microbiota members, are presented as indispensable tools to study fabric–skin–microbe interactions under physiologically relevant conditions. These models enable accurate assessment of antimicrobial efficacy, biocompatibility, and microbiome impact, providing a bridge between in vitro and clinical outcomes. Furthermore, the potential of bioactive textiles in managing microbiome-related skin conditions, such as atopic dermatitis and acne, is discussed alongside the importance of developing microbiome-safe materials. Despite encouraging clinical evidence demonstrating pathogen reduction and symptomatic improvement, the successful translation of these materials to clinical practice needs interdisciplinary research and the adoption of advanced preclinical strategies to ensure innovative solutions for personalized skin health.